TikTok Marketing and Impulse Buying Behavior Among Gen Z Consumers: A Case Study of SHEIN Malaysia - Paul Dung Gadi; Oh Zi Jian; Brahmmanand Sharma; Wei Xin Lee Lee; Xuan Yee Lee; Yun Qi Lee; Zhi Wei Lee; Pawni Sharma; Suraj Shukla; Daisy Mui Hung Kee (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2026)
This study investigates the impact of TikTok marketing campaigns on impulse purchasing among Generation Z Malaysian consumers, specifically the fast-fashion retailer SHEIN. It seeks to uncover which aspects of marketing, including influencer endorsement, entertainment value, scarcity signals, and personalized recommendation, have the greatest impact on impulse buying intention. A quantitative method was undertaken by conducting an online survey of 200 Gen Z consumers to gather behavioral data. Results reveal the significant push of impulse buying by TikTok marketing, driven foremost by emotional excitement and felt urgency generated by influencer credibility and time-limited deals. Entertainment and content genuineness were also revealed to boost consumers' confidence and interaction towards the brand. Implications are drawn that the interactive TikTok environment weakens consumers' cognitive inhibiting power, inviting spontaneous, emotionally driven buying decisions. Findings present useful lessons for marketers that short video is required to enhance interaction and sales rate, and draw attention to the importance of responsible marketing communication targeting youth digital consumers